State Corporatism in Village Development Planning - Gregorius Sahdan; Minardi Minardi; Mohamad Firdaus; Junior Hendri Wijaya (Jurnal Ilmu Sosial dan Humaniora, 2023)
This study departs from the problem that state corporatism is the biggest challenge in realizing village authority. The study of state corporatism has been considered obsolete along with the collapse of authoritarian regimes and governments. After authoritarianism in Indonesia, especially after the enactment of Law No. 6 of 2014 on Villages, state corporatism is very strong in gripping village authority. The question posed in this study is to what extent is state corporatism threatening village authority? Wes used exploratory qualitative methods with case study techniques in Bogem Village, Klaten Regency, Central Java Province, to answer this question—data wes collected by observation, in-depth interviews, and document collection. Data analysis uses triangulation techniques, and findings use interpretive and contextual analysis techniques. Wes found that the state carries out two strategies in corporatism toward villages, namely, a bifrontal strategy and a segmentary strategy. Through these two strategies, village authority and autonomy are weakened in the face of strengthening the grip of the state or village government through various supra-village programs and policies towards villages.